Biomechanics Study on Volleyball Lower Serve Technique: The Influence of Body Angle and Foot Position, Sports Education Students of UMKT - Walhidayat, Bayu; Raharja , Andri Tria (Journal of Educational Sciences, 2025)
The purpose of this research is to study and analyze the biomechanics that affect the lower serve technique. This research focuses on the body angle and position of the player's feet when serving down, and the purpose of this research is to gain a better understanding of the parts that affect the performance of the lower serve technique with a better level of precision.The type of research used by researchers is a quantitative method, using a descriptive quantitative approach. The instrument used is a handphone camera, can use a laptop equipped with the Kinovea 2023 version 1 application. 2 to record video. This application will serve to measure the angle of the body and legs when serving down in a volleyball game. object 1 produces a body angle of 112.8 °, as for the distance between the front and back legs 102.66 cm and a foot angle of 57.4 ° at the time of the ball's contact with the hand. object 2 data results produce a body angle of 93.1°, for the distance between the front and back feet produces a smaller distance compared to object 1 with a distance of 90.34 cm. the success of the lower serve that achieves effectiveness and also precision, is that objects with larger body angles and foot distances tend to successfully pass the ball across the net, while objects with smaller angles and foot distances experience failure.